Safety of Single-Dose Primaquine in G6PD-Deficient and G6PD-Normal Males in Mali Without Malaria: An Open-Label, Phase 1, Dose-Adjustment Trial. (12th January 2018) - Chen, Ingrid; Diawara, Halimatou; Mahamar, Almahamoudou; Sanogo, Koualy; Keita, Sekouba; Kone, Daouda; Diarra, Kalifa; Djimde, Moussa; Keita, Mohamed; Brown, Joelle; Roh, Michelle E; Hwang, Jimee; et al.
Abstract: Background: The World Health Organization recommendation on the use of a single low dose of primaquine (SLD-PQ) to reduce Plasmodium falciparum malaria transmission requires more safety data. Methods: We conducted an open-label, nonrandomized, dose-adjustment trial of the safety of 3 single doses of primaquine in glucose-6-phosphate dehydrogenase (G6PD)-deficient adult males in Mali, followed by an assessment of safety in G6PD-deficient boys aged 11–17 years and those aged 5–10 years, including G6PD-normal control groups. The primary outcome was the greatest within-person percentage drop in hemoglobin concentration within 10 days after treatment. Results: Fifty-one participants were included in analysis. G6PD-deficient adult males received 0.40, 0.45, or 0.50 mg/kg of SLD-PQ. G6PD-deficient boys received 0.40 mg/kg of SLD-PQ. There was no evidence of symptomatic hemolysis, and adverse events considered related to study drug (n = 4) were mild. The mean largest within-person percentage change in hemoglobin level between days 0 and 10 was −9.7% (95% confidence interval [CI], −13.5% to −5.90%) in G6PD-deficient adults receiving 0.50 mg/kg of SLD-PQ, −11.5% (95% CI, −16.1% to −6.96%) in G6PD-deficient boys aged 11–17 years, and −9.61% (95% CI, −7.59% to −13.9%) in G6PD-deficient boys aged 5–10 years. The lowest hemoglobin concentration at any point during the study was 92 g/L. Conclusion: SLD-PQ doses between 0.40 and 0.50 mg/kg were well tolerated in G6PD-deficient males in Mali. Clinical Trials Registration: NCT02535767. Abstract : This phase 1, open-label, nonrandomized, dose-adjustment trial showed that single doses of primaquine between 0.40 and 0.50 mg/kg were well tolerated in G6PD-deficient and G6PD-normal males in Mali, supporting the World Health Organization recommendation on the use of a single low of dose primaquine to reduce Plasmodium falciparum malaria transmission.